YY1-induced long non-coding RNA PSMA3 antisense RNA 1 functions as a competing endogenous RNA for microRNA 214-5p to expedite the viability and restrict the apoptosis of bladder cancer cells via regulating programmed cell death-ligand 1. Issue 2 (20th December 2021) - Zhang, Mingran; Xu, Yunfeng; Yin, Shuai; Qiu, Feng
ABSTRACT: Bladder cancer (BC) is one of the most common malignant tumors in the urinary system. Our research aimed to explore the function and underlying mechanisms of long noncoding RNA (lncRNA) PSMA3-AS1 in BC. RT-qPCR was utilized to detect the levels of PSMA3-AS1, miR-214-5p, and PD-L1. ChIP assay was employed to confirm the transcription factor of PSMA3-AS1. Luciferase reporter assay was carried out to demonstrate the relationships between miR-214-5p and PSMA3-AS1 or PD-L1. The diagnostic value of PSMA3-AS1 was evaluated by the ROC curve. CCK-8, wound healing, transwell, and flow cytometry assays were applied to analyze cell viability, migration, invasion, and apoptosis. Western blotting was used to confirm the expression of cleaved caspase-3. The present study revealed that BC tissues and cells exhibited an increased expression in PSMA3-AS1. High expression of PSMA3-AS1 was related to poor prognosis in BC patients. Then, the area under the ROC curve for PSMA3-AS1 was up to 0.8954. Moreover, ChIP assay elaborated that YY1 could bind to the PSMA3-AS1 promoter region. Furthermore, it was found that that PSMA3-AS1 knockdown repressed BC cell viability and metastasis, and promoted apoptosis. In addition, miR-214-5p was inversely correlated with PSMA3-AS1 or PD-L1 levels. MiR-214-5p deletion reversed the impacts of PSMA3-AS1 deletion on BC progression, and PD-L1 inhibition also abrogated the influence of miR-214-5p deletion in BC development. In conclusion, YY1-induced PSMA3-AS1 exerted an oncogenic function in BC cells via targeting miR-214-5p and enhancing PD-L1, providing potential biomarkers for BC therapy.